166: Using Electronic Medical Records to Estimate Overweight and Obesity Rates in Children in Ontario, Canada. Issue 6 (1st June 2014) - Birken, C; Tu, K; Oud, W; Carsley, S; Hanna, M; Lebovic, G; Guttmann, A
Abstract: BACKGROUND: Few population-based systems exist to monitor child obesity prevalence in Canada. Data from electronic medical records (EMR) have been used in a small number of juridstictions worldwide to estimate obesity prevalence in children. OBJECTIVES: To determine the frequency of height and weight documentation in EMRs in children, to describe the prevalence of child overweight and obesity, by age, and sex using data from the Electronic Medical Record Administrative data Linked Database (EMRALD) database in Ontario, and to determine if there are differences in prevalence based on visit type (well-child visit vs. other). DESIGN/METHODS: We abstracted height and weight in children zero to 19 years of age in EMRALD who had at least one well-child visit from January 2010 to December 2011. Using the most recent visit with both a documented height and weight, we reported the proportion and 95% CIs of subjects defined as overweight, and obese, by age group and sex, using the WHO growth reference standards. We compared the proportion or overweight and obese children by visit type for all age groups, using χ 2 tests. RESULTS: There were 28, 083 well-child visits in 7705 children over this study period. 84.7% of children who attended well-child visits had both a height and weight documented. The prevalence of overweight and obesity, varied by age group from 12% to 32%, and 2% to 12%, respectively. Obesity rates were significantly higher in one- to four-year-olds compared to children <1 year of age (6.1% vs. 2.3%), and in 10- to 14-year-olds compared to five- to nine-year-olds (12% vs. 9%). Both one- to four-year-old (7.2% vs. 4.9%) and 10- to 14-year-old boys (14.5% vs. 9.6%) had higher obesity rates. The proportion of overweight and obese children was higher using heights and weights reported from other child visit types, compared to well-child visits, for all age groups (P<0.05), except for children less than one year of age (P=0.45). CONCLUSIONS: We documented a high rate of overweight and obesity in children. EMR may be a useful tool to conduct population-based surveillance of child overweight and obesity in Canada. The selection of visit type may be an important methodological consideration.